Connecting to God: Nurturing Spirituality through Small Groups - Ware, Corinne (Rowman & Littlefield Publishers, 1997)
Although spiritual growth occurs within an individual, Ware explains that it is the calling of the congregation to be a community of support and encouragement. Indeed, it is amidst the support of a group that an individual learns how to live out personal faith. Ware provides a very practical and accessible model of spiritual formation for self-directing groups that can be led by clergy or laity. Includes thorough guidelines, do's and don'ts, and ground rules for the successful pursuit of spiritual growth in small groups